Preparation of Porous Hydroxyapatite as Synthetic Scaffold Using Powder Deposition and Sintering and Cytotoxicity Evaluation - Pujiyanto, Eko; Tontowi, Alva Edy; Wildan, Muhammad Waziz; Siswomihardjo, Widowati (Trans Tech Publications, Switzerland, 2013)
This study prepared porous hydroxyapatite (porous HA) as synthetic scaffold and find out chemical properties, porosity, compressive strength and cytotoxicity properties. Porous HA was prepared by powder deposition and sintering from HA-PMMA mixed powder. Porous HA characterizations were conducted by XRD, XRF, SEM-EDX and mercury porosimetry analysis. In vitro cytotoxicity testing of porous HA was conducted by MTT method using vero cells. Porous HA has porosity on the interval 62.79 to 69.67% and compressive strength on the interval 1.53 to 3.71 MPa. Optimal porous HA has porosity is 62.79% with compressive strength is 3.71 MPa. Mercury porosimetry analysis showed that optimal porous HA has interconnective porosity up to 88.25% with pore size on the interval 0.05-355 μm and median pore is 52.64 μm. There was no significantly difference in the death percentage of vero cells caused HA powder and optimal porous HA (p= 0.158) but concentration of optimal porous HA were significantly effect on the percentage of vero cells death (p=0.003).